Integrity: A Cornerstone in Teaching English to Indonesian University Students - Haswani, Fahri Haswani; Ariyatna, Ariyatna; Rika, Rika (Universitas Negeri Medan, 2024)
This research investigates the pivotal role of integrity in the English language teaching (ELT) context of Indonesian universities. It explores the concept of integrity within the classroom, its impact on student learning, and the strategies employed by teachers to cultivate integrity among students. By examining the correlation between teacher integrity and student outcomes, this study aims to underscore the significance of ethical conduct in fostering a conducive learning environment. Findings from this research are expected to provide valuable insights for educators, policymakers, and curriculum developers in enhancing the quality of English language education in Indonesia